United or divided? Towns and rural areas in Sweden’s mid-sized municipalities: What do Parliamentary elections between 2006 and 2014 say? - Holmström Zenk, Jesper (Linköping University, 2018)
Sweden has a divided pattern in terms of voting patterns from region to region in terms of the urban/rural divide in the 2006-14 three-time election cycle. The country’s mid-sized municipalities outside of the three major metropolitan areas show a general likelihood to vote for the left-leaning red-green coalition than to vote for the centre-right “alliance” in the urban areas. On the contrary, the alliance had a general advantage on the countryside or in minor locations in said municipalities. Out of the 31 municipalities studied, regional variations are significant. Northern municipalities, while left-leaning in both demographic groups, saw a general trend of the red-green parties winning more relative votes outside of the urban centres. This went heavily against the rest of the country’s tendencies, while southern Sweden also saw many towns vote for the alliance over the red-greens, especially in 2010.

The study confirmed that towns and rural areas are moving further apart, especially when considering the influence of the social conservative and nationalist Sweden Democrats on the rural areas. The Social Democratic party has instead become ever more dependent on urban voters during the eight years of opposition to the alliance between ’06 and ’14. The other main party of Sweden, namely the Moderates was slightly stronger in towns than rural areas in ’06, before shifting in a slightly more rural-dependent direction in the forthcoming elections.

The scope of the study covered all eight parliamentary parties elected into the Swedish Riksdag in 2014. The findings did indicate tendencies for several of them in the electoral research being done around that election. Areas with lower trust in the political system, lower political personal interest, sense of direction of the country going in the wrong direction and low trust ratings for the European Union were linked with rural areas, where the Sweden Democrats gained strong support as an anti-establishment party. Interestingly, in spite of a larger number of the Swedish electorate self-identifying as to the right rather than to the left, the strong divide of right-leaning voters between the alliance parties and the Sweden Democrats contributed to a minority left-leaning government led by the Social Democrats being able to take office after the 2014 election. This study has helped identify and confirm regional and demographical differences between parties and has correlated well with previous findings.

The Excel file contains results for Towns and Rural areas for the years of 2006, 2010 and 2014.

The dataset was originally published in DiVA and moved to SND in 2024.

Excel-filen innehåller valresultat för stad och landsbygd för åren 2006, 2010 och 2014. Se engelsk beskrivning för ytterligare info.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Enade eller delade? Stad och land i Sveriges mellanstora kommuner: Vad säger riksdagsvalen 2006 till 2014?
Keywords: elections; val (samhälleliga händelser); politics; politik; opinion polls; opinionsundersökning; general elections; riksdagsval; Political Science; Statsvetenskap